26. TELEMEDICINE IN ENHANCING THE CAPACITY OF MEDICAL STUDENTS AND STAFF: A SCOPING REVIEW (Vietnam Journal of Community Medicine, 2023)
Currently, one of the prominent applications of information technology in medicine is telemedicine.Objectives: The study aims to summarize the modalities and results of applying telemedicine inmedical training and capacity building of health workers.Methods: We searched for telemedicine and medical education keywords on the Pubmed database.Results: 22 studies met the inclusion criteria. Most studies describe telemedicine apps that usephones, apps. For most of the study, medical students examined and cared for patients remotelywhile improving their telemedicine skills to interpret health exam results.Conclusion: Previous studies show that all technological approaches enhance knowledge, skills andattitudes, and pure e-learning is comparable to face-to-face training.
Keywords: Telemedicine, training, medicine, students, healthcare workers.